2023
DOI: 10.1186/s12933-023-01774-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and gestational diabetes reprogram the methylome of offspring beyond birth by inducing epigenetic signatures in metabolic and developmental pathways

Abstract: Background Obesity is a negative chronic metabolic health condition that represents an additional risk for the development of multiple pathologies. Epidemiological studies have shown how maternal obesity or gestational diabetes mellitus during pregnancy constitute serious risk factors in relation to the appearance of cardiometabolic diseases in the offspring. Furthermore, epigenetic remodelling may help explain the molecular mechanisms that underlie these epidemiological findings. Thus, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…It is already known that adiponectin and leptin gene expression is controlled by histone modifications and thus suggesting its implication on fetal metabolism and development [20,21]. Alba-Linares et al found that maternal obesity and maternal obesity with gestational diabetes led to abundant DNA methylation alteration during the first six months of child development into the genes including CPT1B, FN3K, SLC35F3, and SLC38A4 involved in the metabolism of fatty acids, mitochondrial bioenergetics, and postnatal development processes [29].…”
Section: Implication Of High Fat Diet and Maternal Obesity On Epigene...mentioning
confidence: 99%
“…It is already known that adiponectin and leptin gene expression is controlled by histone modifications and thus suggesting its implication on fetal metabolism and development [20,21]. Alba-Linares et al found that maternal obesity and maternal obesity with gestational diabetes led to abundant DNA methylation alteration during the first six months of child development into the genes including CPT1B, FN3K, SLC35F3, and SLC38A4 involved in the metabolism of fatty acids, mitochondrial bioenergetics, and postnatal development processes [29].…”
Section: Implication Of High Fat Diet and Maternal Obesity On Epigene...mentioning
confidence: 99%
“…For example, maternal obesity was associated with altered histone methylation during embryonic development and histone H3 Lysine 4 dimethylation (H3K4me2) was reduced in the embryos of obese mice (Pan et al, 2020). Epigenetic studies using human blood samples have demonstrated that both maternal diabetes and obesity can reprogram the DNA methylome of newborns or offspring beyond birth (Alba‐Linares et al, 2023; Rizzo et al, 2020). Thus, while maternal metabolic disorders can negatively influence fetal and offspring development through epigenetic alterations, the effects may be preventable or even reversible.…”
Section: Epigenetic Mechanisms Underlie Ofcs and Related Birth Defect...mentioning
confidence: 99%
“…There is evidence that systemic intrauterine fetal programming displays hallmarks of trained immunity, in particular epigenetic changes, which are critical in the transmission of cardiometabolic disease from mothers to their offspring (reviewed in 48 ). For example, a recent study found that DNA methylation biomarkers in peripheral blood cells maintained across the first year of life could discriminate children born to mothers who suffered from obesity or gestational diabetes, and crucially, these alterations affected genes related to immune system activation ( ETS1, ITGB2 , and TNF family), metabolism ( FN3K, SLC38A4, SLC35F3 , and CPT1B ), and epigenetics ( HDAC4, PRDM16 ) 49 . Maternal obesity and diabetes could constitute serious risk factors in relation to the appearance of cardiometabolic diseases in the offspring and it remains to be studied whether parental trained immunity is transmitted across generations to predispose offspring to cardiometabolic diseases.…”
Section: Trained Immunity In Cardiometabolic Diseasesmentioning
confidence: 99%
“…For example, a recent study found that DNA methylation biomarkers in peripheral blood cells maintained across the first year of life could discriminate children born to mothers who suffered from obesity or gestational diabetes, and crucially, these alterations affected genes related to immune system activation ( ETS1, ITGB2 , and TNF family), metabolism ( FN3K, SLC38A4, SLC35F3 , and CPT1B ), and epigenetics ( HDAC4, PRDM16 ). 49 Maternal obesity and diabetes could constitute serious risk factors in relation to the appearance of cardiometabolic diseases in the offspring and it remains to be studied whether parental trained immunity is transmitted across generations to predispose offspring to cardiometabolic diseases. If proven, the identification and treatment of trained immunity in cardiometabolic diseases in women of childbearing age could help mitigate the acquisition of trained immunity and its associated risk of cardiovascular disease in the next generation.…”
Section: Trained Immunity In Cardiometabolic Diseasesmentioning
confidence: 99%